Tumour, node and metastasis stage, tumour grade, lymph node ratio, surgical margin, and oestrogen receptor status are significant predictors of breast cancer recurrence - Hussin, Huzlinda; Abdul Kahar, Nor Farahin; Baharom, Zuliatul Faizah (Universiti Putra Malaysia Press, 2024)
Background: Prognostic factors play a crucial role in shaping treatment decisions as outlined in breast cancer clinical guidelines. Despite extensive large-scale cohort studies on the risks of prognostic factors for breast cancer recurrence, local research on this subject has been comparatively limited. This study aimed to identify the risk of prognostic factors associated with breast cancer recurrence. Methods: This retrospective study examined prognostic factors, including age at diagnosis, tumour stage and grade, lymph node ratio (LNR), surgical margin status, lymphovascular invasion (LVI), hormone receptor status, and treatment received in 184 breast cancer patients. Recurrence-free survival (RFS) was evaluated using Kaplan-Meier analysis, and multivariate Cox regression analysis was applied to assess the risk of breast cancer recurrence. Results: Sixty patients (32.6%) experienced breast cancer recurrence, with a median recurrence time of 18 months. Kaplan-Meier analysis demonstrated that TNM stage III, pT3 stage, grade 3, high LNR (>0.65), positive surgical margin, presence of LVI, negative ER and PR status, and surgery alone without any adjuvant treatment were all associated with significantly worse RFS (p < 0.05). Multivariate Cox regression analysis revealed that TNM stage II and grade 3 tumour, high LNR, positive surgical margin, and negative ER status were independent prognostic factors for breast cancer recurrence. Conclusion: Higher TNM stage, higher tumour grade, high LNR, positive surgical margin, and negative ER status are significant predictors of breast cancer recurrence. Recognising these prognostic factors provides valuable insights for shaping future treatment approaches.